Bacteroides Microbial Source Tracking Markers Perform Poorly in Predicting Enterobacteriaceae and Enteric Pathogen Contamination of Cow Milk Products and Milk-Containing Infant Food - Tsai, Kevin; Hoffmann, Vivian; Simiyu, Sheillah; Cumming, Oliver; Borsay, Glorie; Baker, Kelly K. (Frontiers in Microbiology, 2022)
Consumption of microbiologically contaminated food is one of the leading causes of diarrheal diseases. Understanding the source of enteric pathogens in food is important to guide effective interventions. Enterobacteriaceae bacterial assays typically used to assess food safety do not shed light on the source. Source-specific Bacteroides microbial source tracking (MST) markers have been proposed as alternative indicators for water fecal contamination assessment but have not been evaluated as an alternative fecal indicator in animal-derived foods. This study tested various milk products collected from vendors in urban Kenyan communities and infant foods made with the milk (n=394 pairs) using conventional culture methods and TaqMan qPCR for enteric pathogens and human and bovine-sourced MST markers. Detection profiles of various enteric pathogens and Bacteroides MST markers in milk products differed from that of milk-containing infant foods. MST markers were more frequently detected in infant food prepared by caregivers, indicating recent contamination events were more likely to occur during food preparation at home. However, Bacteroides MST markers had lower sensitivity in detecting enteric pathogens in food than traditional Enterobacteriaceae indicators. Bacteroides MST markers tested in this study were not associated with the detection of culturable Salmonella enterica and Shigella sonnei in milk products or milk-containing infant food. The findings show that while Bacteroides MST markers could provide valuable information about how foods become contaminated, they may not be suitable for predicting the origin of the enteric pathogen contamination sources.